Level of Knowledge on Kangaroo Mother Care and Its Associated Factors Among Postnatal Mothers With Preterm Babies in Central Tanzania: Hospital-Based Cross-Sectional Study - Naomi Chamhene BScN, MScPN; Fabiola Vincent Moshi DipEd, BScN, MaHPM, PhD (SAGE Open Nursing, 2023)
Introduction Kangaroo mother care (KMC) has been proven to reduce preterm babies’ deaths by 40%. The study aimed at assessing the prevalence and predictors of knowledge about KMC among postnatal mothers of preterm babies in the Central zone, Tanzania. Objective To assess the level of knowledge about KMC and its associated factors. Methods It was an analytical cross-sectional study involving 363 mothers of preterm babies from the Central zone. All mothers admitted during data collection and who met the inclusion criteria were enrolled until the sample size was attained. A structured questionnaire was used for data collection. Data were analyzed using SPSS v23. Descriptive statistics were used to describe the study variable while inferential statistics (univariate and multivariate analyses) were used to determine the predictors of knowledge. Results Only 138(38%) postnatal mothers had adequate knowledge about KMC . Factors associated with knowledge on KMC were the age of the mother (those aged ≥30 years were almost four times more likely to have adequate knowledge compared to those aged <20 years [ P   =  .044]), level of education of the mother (women who had secondary education and above were six times more likely to have adequate knowledge on KMC compared with those with no formal education [ P  < .001) and the family type of a postnatal mother living in (those living in a nuclear families were 48% less likely to have adequate knowledge if compared with those living in extended families [ P   =  .012]). Conclusion Less than half of the interviewed postdelivery women had adequate knowledge of KMC. Postdelivery women who were more likely to have adequate knowledge about KMC were those aged more than 30 years, with a higher level of education, and living in extended families. We recommend a deliberate effort on improving postnatal mothers’ knowledge of KMC, one of the strategies being initiating care of preterm babies in the antenatal package to prepare these mothers.